Suicidal ideation and coping strategies against early pregnancy in a hospital in metropolitan Lima - Hilaquita Cruz, Gerson (2018)
Objective: The objective of this research is to determine the relationship between suicidal ideation and coping strategies against pregnancy in adolescent mothers in a national hospital in metropolitan Lima. Material and Methods: A non - experimental, cross - sectional correlational design was used. It was carried out in a group of 140 pregnant adolescents between 13 and 18 years old. The instruments used were the Suicidal Ideation Scale (SSI) of Beck, adapted in Peru by Eugenio and Zelada (2011) and the Adolescent Coping Scale (ACS) of Frydenberg and Lewis, adapted by Canessa in 2002. Results: The results obtained show that there is a highly significant negative relationship between suicidal ideation and fifteen of the coping strategies (rho = -0.562 ** p <0.05). Conclusions: Therefore, it is concluded that the greater the use of coping strategies, the lower the risk of suicidal ideation and vice versa.